2021
DOI: 10.1016/j.socscimed.2021.113966
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and misconceptions in the time of the COVID-19 pandemic: A field experiment in India

Abstract: A hidden cost of the COVID-19 pandemic is the stigma associated with the disease for those infected and groups that are considered as more likely to be infected. This paper examines whether the provision of accurate and focused information about COVID-19 from a reliable source can reduce stigmatization. We carry out a randomized field experiment in the state of Uttar Pradesh, India, in which we provide an information brief about COVID-19 by phone to a random subsample of participants to address stigma and misc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 52 publications
1
47
0
3
Order By: Relevance
“…We used reading and writing to intervene in the perceived discrimination of an individual. Previous studies have confirmed that epidemic outbreaks have been historically accompanied by stigma, discrimination, and xenophobia, leading to psychological harm to individuals in the epicenter (Villa et al, 2020 ). Therefore, psychological interventions that reduce the perceived discrimination in the people exposed to the pandemic could be helpful in preventing the development of mental illnesses.…”
Section: Discussionmentioning
confidence: 90%
“…We used reading and writing to intervene in the perceived discrimination of an individual. Previous studies have confirmed that epidemic outbreaks have been historically accompanied by stigma, discrimination, and xenophobia, leading to psychological harm to individuals in the epicenter (Villa et al, 2020 ). Therefore, psychological interventions that reduce the perceived discrimination in the people exposed to the pandemic could be helpful in preventing the development of mental illnesses.…”
Section: Discussionmentioning
confidence: 90%
“…Minimnya dukungan sosial kepada pengidap covid-19 serta keluarga menimbulkan masalah baru pada penderita dan keluarga, dimana mereka akan merasakan kesepian, ketidakpercayaan terhadap masyarakat, perasaan kehilangan teman (Dubey et al, 2020;Ghosh et al, 2020 Hasil penelitian ini menemukan bahwa terdapat pengaruh bahwa tingkat pengetahuan akan mempengaruhi cara seseorang memandang orang yang terinfeksi covid-19. Hal ini sejalan dengan penelitian yang dilakukan oleh Islam et al, (2021) yang melakukan uji lapangan secara acak di negara bagian Uttar Pradesh, India. Hasil penelitian bahwa informasi singkat mengurangi stigma terhadap pasien covid-19 dan kelompok-kelompok tertentu seperti agama minoritas, kelompok kasta bawah, dan pekerja garis depan (kesehatan, polisi), dan mengurangi keyakinan bahwa kasus infeksi lebih banyak terjadi di kalangan sosial dan ekonomi tertentu yang terpinggirkan seperti muslim, kasta rendah, penduduk pedesaan yang miskin.…”
Section: Pembahasanunclassified
“…Globally extrapolated and frequently at grave individual hazard, health-care professionals in almost every country have been devotedly toiling on the front lines treating COVID-19 victims, but have not at all times garnered the recognition they are entitled to regardless of their substantial interventions [ 7 ]. Over and above, primary health-care personnel run a correspondingly heightened risk of disease, along with incurring unfavorable emotional responses through apprehension, avoidance of contagion or a sense of helplessness positioning them at an additional frontline characterized by emotional vulnerability towards such a relentless worldwide health-care emergency [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%